Sir Cecil Looker interviewed by Alan Hodgart - Looker, Cecil, 1913-1988; Hodgart, Alan (1975)
Looker speaks about his childhood; his first job in 1932; studying at Sydney University; joining the Commonwealth Public Service in 1937; working as private secretary to Lord Casey; declaration of World War II; working as Menzies private secretary; Naval Intelligent Officer, 1942-1945, working as stockbroker and underwriter with Ian Potter & Co.; operation of Stock Exchange; changes he implemented while Chairman of the Melbourne Stock Exchange and President of the Australian Associated Stock Exchanges; his other public positions; 1969-71 mining boom; the Rae Report; regulation of the stock market; and the future of the Stock Exchange.
Recorded in Melbourne.
Also available online
Timed summary and uncorrected transcript (typescript, 152 leaves) available.
Keywords: Looker, Cecil, -- 1913-1988 -- Interviews; Australian Stock Exchange; Australian Associated Stock Exchanges; Stockbrokers -- Australia -- Interviews; Stock exchanges -- Law and legislation -- Australia; Stock exchanges -- Australia; Australia -- Politics and government -- 1922-1945.